Pengaruh Dosis Koagulan Belimbing Wuluh Serta Pengaruh pH Dalam Menyisihkan Warna Dan Zat Organik Pada Air Gambut - Lisa Asmiyarna; Syarfi Daud; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Peat water in Indonesia has the potential a source of clean water because of its ample availability, but in terms of qualitatively it still does not meet the standards of clean water quality according to Permenkes No. 32 of 2017, such as organic substances and colors that are still high. This weakness can be overcome through processing using the coagulationflocculation method with the addition of natural coagulants. One of the natural coagulants that can be used in the coagulation-flocculation process is averrhoa bilimbi. Averhhoa bilimbi as a coagulant can reduce color parameters and organic matter in peat water because it has advantages in the coagulation-flocculation process due to its high acid concentration. This study aims to determine the effect of averrhoa bilimbi coagulant dosage and pH in removing organic matter and color in peat water. Keywords: Peat Water, Dosage, pH, Coagulation-Floculation, Averrhoa bilimbi.